Expression and function of syndecan-4 in human platelets - Kaneider, Nicole C.; Feistritzer, Clemens; Gritti, Donatella; Mosheimer, Birgit A.; Ricevuti, Giovanni; Patsch, Josef R.; Wiedermann, Christian J. (Thrombosis and Haemostasis, 2005)
Platelet recruitment crucially depends on amplification systems provided by autocrine and paracrine factors such as adenosine diphosphate. In inflammatory states, consumption of coagulation proteins, such as antithrombin aggravates the procoagulant state. In this study, we report that platelets express synde-can-4, an antithrombin-binding cell surface heparan sulphate proteoglycan, whose ligation with antithrombin inhibits activated platelet-dependent superoxide anion release from neut-rophils by the limitation of adenosine diphosphate and adeno-sine triphosphate secretion in activated platelets. Adenosine triphosphate-induced platelet aggregation is reduced after treatment of platelets with antithrombin, which is reversed by blockade of syndecan-4. We further observed that antithrombin limits CD40 ligand expression in adenosine diphosphate-activated platelets and inhibits the shedding of syndecan-4 from activated platelets. Syndecan-4 appears to be directly involved in regulating platelet aggregation as anti-syndecan-4 antibody augments platelet aggregation. We suggest that antithrombin might exert beneficial effects in disseminated intravascular coagulation by reducing platelet activation, observed as inhibited CD40 ligand expression, syndecan-4 shedding, and adenosine diphosphate- and adenosine triphosphate-release from activated platelets with subsequent inhibition of neutrophil respiratory burst. From these data it is concluded that syndecan-4 may play important roles in the regulation of inflammatory effects of platelets.
Keywords: Cell-cell interactions; disseminated intravascular coagulation (DIC) / sepsis; antithrombin; heparins / glycosaminoglycans; platelet pharmacology